Hydration reaction analysis of calcium-silicatebased materials using scanning electron microscopy and X-ray diffraction method - Mutluay Abidin Talha; Mutluay Merve; Pehlivanli Adem (Balkan Stomatological Society, 2022)
Background/Aim: The components of calcium silicate-based materials can be identified through X-Ray Diffraction Analysis. This study aimed to determine the hydration reactions and particle size of MTA Angelus, Biodentine, and NeoMTA Plus as calcium-silicate-based materials. Material and Methods: The powder and set cement samples using divergence and scatter slits of 1○ and a receiver slit of 0.10 mm. The scanning range was set at 5○ to 70○, and ongoing scans for the theta-2theta range was performed with a scan speed of 2○/minute (-1). The patterns obtained were analyzed using search-match software. The three most substantial peaks were used to identify hydration reactions and major crystalline structures. Also, Scanning Electron Microscope (SEM) analysis was performed and the particle size of set materials were determined using an image analysis software. Results: According to X-Ray Diffraction Analysis, the main components were determined as tricalcium silicate and dicalcium silicate in the three calcium silicate-based materials. We determined that the main components of the materials were similar. We also identified the extensive presence of tricalcium aluminate in MTA Angelus, calcium carbonate in Biodentine, and calcium phosphate salts in NeoMTA Plus. Furthermore, the results of the present particle analysis show that the calcium-silicate-based materials' distribution of particle count and size varies. Biodentine has the widest, and MTA Angelus has the narrowest particle size distribution range. NeoMTA Plus has the largest number of fine, large-sized particles (p < 0.0001), while MTA Angelus and Biodentine have a more homogeneous and nonstatistically significant particle distribution range (p > 0.05). Conclusions: The present findings provide insight into variations in performance between different calcium-silicate-based materials.